Design of chitosan and alginate emulsion-based formulations for the production of monolayer crosslinked edible films and coatings - Vieira, Tiago M. (2021)
This study aimed to develop edible monolayer emulsion-based barriers with polysaccharides as film-forming components (chitosan and sodium alginate), soy lecithin as a surfactant and olive oil as a hydrophobic barrier. Monolayer barriers in the form of films were prepared by casting filmogenic emulsions composed of 2% w/v chitosan (dissolved in lactic acid 1% v/v) or 1% w/v sodium alginate, with different lipid contents (25, 50 and 100% w/w biopolymer basis) and different surfactant concentrations (5, 10 and 25% w/w, lipid basis). Glycerol was used as a plasticizer (25 % w/w, biopolymer basis). After the emulsion drying process, the obtained stand-alone films were sprayed with a crosslinking solution, achieving an optimized crosslinker content of 3.2 mgCa2+/cm2 alginate film and 4 mg tripolyphosphate/cm2 chitosan film. The effect of oil and lecithin contents, as well the presence of crosslinking agents, on the film’s water vapour permeability (WVP), water vapour sorption capacity, mechanical properties and colour parameters, was evaluated. The results have shown that the lowest WVP values were obtained with formulations containing 25% lipid and 25% surfactant for chitosan films, and 100% lipid and 25% surfactant for alginate films. The application of the crosslinking agents decreased even further the WVP, especially for chitosan films (by 30%). Crosslinking also increased films’ resistance to deformation under tensile tests. Overall, the films developed present a good potential as polysaccharide-based barriers with increased resistance to water, which envisages the use of the designed formulations to produce either edible/biodegradable films or edible coatings